ANALISIS KELAYAKAN FINANSIAL USAHA TANAMAN HIAS DI KOTA SAMARINDA (Analysis of Financial Feasibility of Ornamental Plants Business in Samarinda City) - ERICK ABDUL MUTAKABBIR; NELLA NAOMI DUAKAJU (Universitas Mulawarman (University of Mulawarman), 2019)
Ornamental plants are commonly planted by people as decoration. This study aimed to determine income and financial feasibility of ornamental plants business in Samarinda City. This study was done in three months since November 2017 until Januari 2018 in Samarinda City. The sampling method used purposive sampling method with the number of samples as many as 29 respondents. The data were collected through interviews with respondents. The assesment of business feasibility was done by using some investment criterias such as Net Present Value (NPV), Internal Rate of Return (IRR), dan Net Benefit Cost Ratio (Net B/C Ratio). The results of this study showed that ornamental plants business in Samarinda City owns the average of investment cost of IDR90,982,931.00 year-1, the average of operating cost of IDR37,307,586.00 year-1, the average of revenue of IDR118,506,206.00 year-1, and the average of income of IDR81,198,620.00 year-1. The assesment results of investment in ornamental plants business in Samarinda City are NPV of IDR75,074,609.00 at discount rate of factor of 12%, IRR of 65%, while Net B/C Ratio of 1,82. This is showed that ornamental plants business in Samarinda City is financially feasible to be done.